Analysis of surgical procedure of four cases of ovarian pregnancies treated with laparoscopic surgery - Yuta Kasahara; Ryo Yokomizo; Kazu Ueda; Rei Makishima; Hiroshi Kishi; Aikou Okamoto (Wolters Kluwer Medknow Publications, 2021)
Ovarian pregnancy is a rare disease, accounting for 0.5%-3% of ectopic pregnancies. Ovarian pregnancy risk factors and preoperative diagnosis have been extensively reported. However, its histopathology and surgical findings have been poorly studied. To examine appropriate surgical procedures, we investigated the clinical features, surgical findings, and histopathological examinations of four ovarian pregnancy cases treated in our hospital. In histopathological examination, most specimens did not contain ovarian tissues; in some cases, villous tissues were buried in a clot. Therefore, evaluating the appropriateness of surgical resection range from histopathological images was difficult. However, the postoperative course was favorable; no cases manifested complications. Considering all these facts, we regarded the surgical procedures of the four cases in this study as appropriate. For the treatment of ovarian pregnancies, especially for the outward development type, a sufficient therapeutic effect may be achieved even without extensive excision of the ovarian tissues by laparoscopic surgery.